Vulcanization Kinetics and Mechanical Properties of Ethylene Propylene Diene Monomer Thermal Insulation - Mohamad Irfan Fathurrohman; Dadi Rusadi Maspanger; Sutrisno Sutrisno (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The vulcanization kinetics of Ethylene-propylene diene monomer (EPDM) rubber thermal insulation was studied by using rheometer under isothermal condition at different temperatures. The rheometry analysis was used to determining the cure kinetic parameters and predicting the cure time of EPDM thermal insulation. The experimental results revealed that the curing curves of EPDM thermal insulation were marching and the optimum curing time decreased with increasing the temperature. The kinetic parameters were determined from the autocatalytic model showed close fitting with the experimental results, indicating suitability of autocatalytic model in characterizing the cure kinetics. The activation energy was determined from the autocatalytic model is 46.3661 kJ mol-1. The cure time were predicted from autocatalytic model and the obtained kinetic parameter by using the relationship among degree of conversion, cure temperature, and cure time. The predictions of cure time provide information for the actual curing characteristic of EPDM thermal insulation. The mechanical properties of EPDM thermal insulation with different vulcanization temperatures showed the same hardness, tensile strength and modulus at 300%, except at temperature 70 °C, while the elongation at breaking point decreased with increasing temperature of vulcanization. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)